SUBJECTIVE PERCEPTION OF EFFORT DURING THE APPLICATION OF THE TEST OF 1RM USING FACIAL SCALE (Fiep Bulletin - online, 2015)
The present research was a descriptive form with correlation delineation and objectified to identify through the attempts used for the accomplishment of the test of a maximum repetition (T1RM) if it had correlation between the percentages of load of attempts in this test with the subjective perception of effort (PSE) when answered by the volunteers using Facial Scale. The study assisted with 12 volunteers between 18 and 30 years old that practice power training three times per week for least the six months during 60 minutes. The results obtained were a correlation between the subjective perception of effort, Facial Scale, and the percentages of the 1RM test from 70% of the maximum capacity of work, express by the maximum kilogram. The treatment of for the regression analysis was based on the procedures of Stepwise Correlations observing itself to a level of significance of p < 0,05, for the acceptance of parametric procedure. Before, we applied Komogrorov-Smirnov's Non-parametric test with the results for superior members of: - KS = 0,907 with sig. p = 0,383 that was > 0,05 for superior member, and KS = 1,026 with sig. p = 0,243 also > 0,50 for inferior members. After the normalization, it can be conclude into two predictable equations one for superior members and one for inferior members, that when it is used they allow to predict how much of the percentage of the maximum load the individual would reach in the 1 RM test from the subjective punctuation in facial scale that the same it selected.
Keywords: Subjective perception of Effort; Test of 1RM; Scale of Faces